A Study on the translation of Vietnamese folk games = Chiến lược dịch các thuật ngữ văn hóa liên quan tới trò chơi dân gian Việt Nam - Trần, Thị Thúy Vượng (2021)
Translating culture-specific items has permanently been a great challenge to translators. As an inevitable consequence, few bilingual books on Vietnamese culture have been published. Being a person who is interested in folk cultures and also a translator, the researcher hopes to contribute to conserving traditional cultural values and promoting them to international friends. These desires inspired her to conduct the thesis “A Study on The Translation of Vietnamese Folk Games”. With an attempt to finger out the most common strategies used in translating culture-specific items related to Vietnamese folk games, the researcher actively sought cultural words on this topic and their translations from available materials. The majority of data was exploited from famous works on Vietnamese folk culture by Huu Ngoc, a proficient translator, to guarantee the reliability of results. Textual analysis, observation and interview were instruments to collect necessary data. Qualitative and quantitative analysis was employed to find answers to research questions. Accordingly, paraphrase by using related words and use loan words or more general concepts are the most common strategies to deal with culture-specific items. Not only does this paper determine the most used translation strategies to tackle with cultural words but it also gives practical glossaries for readers who are interested in folk culture. The researcher does expect that her work will stimulate further studies on the subject